2022
DOI: 10.3389/fncir.2022.980631
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal avalanche dynamics and functional connectivity elucidate information propagation in vitro

Abstract: Cascading activity is commonly observed in complex dynamical systems, including networks of biological neurons, and how these cascades spread through the system is reliant on how the elements of the system are connected and organized. In this work, we studied networks of neurons as they matured over 50 days in vitro and evaluated both their dynamics and their functional connectivity structures by observing their electrophysiological activity using microelectrode array recordings. Correlations were obtained bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Neurons within the six four-nodal devices self-organized into highly complex networks by 14 DIV ( Figure 1A ). At this stage, electrophysiological recordings furthermore indicated that spontaneous neural activity had started transitioning from immature tonic firing to synchronous bursting within the nodes, consistent with previous findings ( Figure 1B ) (1, 3, 20, 40, 41).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Neurons within the six four-nodal devices self-organized into highly complex networks by 14 DIV ( Figure 1A ). At this stage, electrophysiological recordings furthermore indicated that spontaneous neural activity had started transitioning from immature tonic firing to synchronous bursting within the nodes, consistent with previous findings ( Figure 1B ) (1, 3, 20, 40, 41).…”
Section: Resultssupporting
confidence: 90%
“…This combined approach can be challenging to implement in vivo . An increasing body of literature, including recent studies from our group, has characterized how in vitro neural networks develop and mature in healthy, i.e., unperturbed, conditions (1, 3, 20, 40, 41). Such studies provide valuable insights into the intrinsic self-organizing behaviour of engineered neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat cortical neurons from Sprague Dawley rats (Gibco, A36511, neuronal purity: 96%) were plated at a density of 1000 cells mm −2 , equalling 20 000 cells per chamber in the two-nodal platforms and 40 000 cells in the controls. This plating density was chosen based on previous studies indicating that at least 250 cells mm −2 are required for networks to establish synchronized activity [46], and that higher densities can lead to more complex activity dynamics [47]. Half the cell media was replaced with fresh cell media 4 h after plating, and again after 24 h. From here on, half the cell media was replaced every second day until the cultures were ended at 28 DIV.…”
Section: Cell Plating and Maintenancementioning
confidence: 99%
“…However, we and others have shown that neural network dynamics at the microscale and mesoscale can be studied with advanced cellular models utilizing the inherent self-organizing properties of neurons into complex, computationally competent networks, akin to networks in the brain (Pasquale, Massobrio et al 2008, Downes, Hammond et al 2012, Poli, Pastore et al 2015, Schroeter, Charlesworth et al 2015, Fiskum, Sandvig et al 2021, Antonello, Varley et al 2022, Heiney, Huse Ramstad et al 2022). Relevant applications of these methods to model ALS have been able to capture signs of hyperexcitability and time-dependent changes in networks of patient derived MNs (Wainger, Kiskinis et al 2014, Ronchi, Buccino et al 2021, Sommer, Rajkumar et al 2022).…”
Section: Introductionmentioning
confidence: 99%